Spatial distribution and epidemiological analysis of leprosy in the 53 municipalities of the Interstate Health Network of the Middle São Francisco Valley (Research, Society and Development, 2023)
Objective: To analyze the spatial distribution of leprosy indicators in the 53 municipalities of the Interstate Health Care Network of the Middle São Francisco Valley (PEBA Network), 2013-2017. Methodology: Ecological study based on data from the Notifiable Diseases Information System - Sinan to calculate the indicators: annual detection rate of new cases of leprosy in the general population, in the population from zero to 14 years old and who present grade 2 of physical disability at the time of diagnosis, the global and local Moran’s indices were used to analyze spatial dependence. Results: The incidence of leprosy in the general population was 37.68/100 thousand inhabitants. In the population aged zero to 14, it was 9.89/100 thousand inhabitants. The rate of leprosy cases with physical disability at diagnosis was 19.56/1 million. Conclusion: The results point to priority areas of action, suggest active transmission and failure in early diagnosis.